C++ for dummies - Davis, Stephen R., 1956-; Safari eBooks (Hoboken, N.J. : Wiley Pub., 2009)
"C++ For Dummies, 6th Edition, helps you understand C++ programming from the ground up. It's full of examples to show you how things work, and it even explains "why", so you understand how the pieces fit together. And the bonus CD includes a special code editor, an update GNU compiler, and all source code from the book to save you time"--Resource description page.
Description based on print version record.
Includes index.
Keywords: C++ (Computer program language); Electronic books